APLIKASI MICROFLUIDIC PAPER-BASED ANALYTICAL DEVICES (µPADS) BERBASIS PENCETAKAN LILIN DALAM KIMIA ANALITIK: A MINI REVIEW - Allfira, Elisse Nur; Masriani, Masriani; Budi, Firman Shantya (Tanjungpura University, 2026)
Wax-printed microfluidic paper-based analytical devices (µPADs) represent a significant innovation in analytical chemistry by providing a low-cost, portable, and user-friendly platform for chemical analysis. This article presents a systematic literature review of the applications of wax-printed µPADs for the detection of various inorganic and organic analytes across diverse sample matrices, including water, food, and biological fluids. The most commonly employed detection methods are colorimetric and distance-based techniques, while fluorometry and electrochemistry have also been applied to enhance sensitivity. The main advantages of these devices include simple fabrication, short analysis time, and low reagent consumption. Nevertheless, several challenges remain, including device stability, limited detection limits, and the need for integration with digital readout systems. Overall, wax-printed µPADs hold great potential as reliable platforms for modern chemical analysis, both for field applications and laboratory-based studies.